Patrimônio gastronômico do RN: construindo a identidade de marca no Turismo - Sant'ana, Romário Oliveira de (2021)
Tourism happens when people are willing to leave their surroundings motivated by peculiarities present in a destination. Typical dishes and products can be easily incorporated as tourist attractions. The tourist is fond of objects that represent the local culture of the visited destination; with the provision of identity foods, the tourist has an element to taste or take with them on the way back home. The importance of tourist attractions as a form of motivation for the arrival of tourists is highlighted. The aim of this study is to analyze the gastronomic heritage of Rio Grande do Norte (RN) - Brazil, in order to build the brand identity. The work developed comprises a field and documentary research with a predominantly qualitative approach and with some quantitative aspects, of an applied nature and exploratory objectives. In order to fulfill the objective of verifying how memory and food identity are perceived from the tourist's perspective, user-generated content (UGC) is used referring to the tourist experience in contact with representative foods from the gastronomic heritage of RN. To investigate the management of gastronomic tourism, speeches were collected in interviews and statements available in press vehicles and official government channels of the actors involved. In data analysis, the IRAMUTEQ software version 0.7 was used for the similarity and word cloud test, in addition to content analysis in relation to the categories of memory, identity and cultural heritage. Results indicate that few governmental actions were taken regarding the protection of the Potiguar gastronomic heritage, while analyzing the UGC, several aspects of memory, identity and heritage are found in the experience of the traveler who experiences regional delicacies. The construction of a brand identity for RN's gastronomic heritage is at an immature moment, demanding public management initiatives that capture the affective potential of memory and identity that already exist in the tourist experience with food.